Effects of green intellectual capital, green accounting, and green innovation on firm value: The moderating role of return on assets - Tri Astuti; Nurmala Ahmar (Environmental Economics)
This study examines the influence of green intellectual capital, green accounting, and green innovation on firm value and return on assets. Green intellectual capital refers to the knowledge and expertise of environmental sustainability, green accounting involves incorporating environmental costs into financial reporting, and green innovation focuses on developing environmentally friendly technologies and processes. Indicators for evaluating these factors include the Green Intellectual Capital Index, Global Reporting Index disclosures for green accounting, and green process and product innovation dimensions for green innovation. The study employs Warp PLS to analyze data from 88 companies listed on the Sustainable and Responsible Investment (SRI-KEHATI) index on the Indonesia Stock Exchange. The findings indicate that green accounting significantly enhances firm value, while green innovation does not show a direct impact. However, all three factors positively influence return on asset (ROA). The moderating role of ROA was found to strengthen the relationship between green intellectual capital and green accounting with firm value, but it did not moderate the effect of green innovation. ROA was used as an indirect financial indicator to formulate the company’s profitability and strategic sustainability planning. These results highlight the importance of embedding sustainability into business strategies to enhance financial and environmental performance.